PENGEMBANGAN JEJARING WIRAUSAHA DALAM MENINGKATKAN KINERJA UNIT USAHA MIKRO KECIL DAN MENENGAH DI KOTA BIMA - Nurul Huda; Sri Syamsinirwani (Fakultas Ekonomi dan Bisnis Universitas Mataram, 2019)
This study aims to see whether Entrepreneurial Networks influence the performance of Micro Small and Medium Enterprises (UMKM) in the City of Bima Does Explorative Learning affect the performance of Micro Small and Medium Enterprises (UMKM) in Bima City, and which of the entrepreneurial networking variables and Exploratory Learning has a dominant influence on the performance of Micro Small and Medium Enterprises (UMKM) in Bima City. This research was conducted on Micro Small and Medium Enterprises (UMKM) in Bima City for 7 (seven) months. This research is divided into several stages, namely 1) Preparation (2) Implementation, (3) Reporting, (4) Monitoring, evaluation, and dissemination. The research method used is explanatory research research using the sample survey approach. Conventionally, explanatory research is used to explain the relationship between variables by testing hypotheses. Questionnaires were distributed to 104 Micro Small and Medium Enterprises (UMKM) in Bima City, where questionnaires were tested for validity and reliability and then processed using SPSS so that the accuracy of the analysis tools could be reliable. The results showed that. Network Enterpreneur affected the performance of Micro Small and Medium Enterprises (UMKM) in Bima City while exploratory learning did not affect the performance of Micro Small and Medium Enterprises (UMKM) in Bima City.